Fully "recombinant enzyme-linked immunosorbent assays" using genetically engineered single-chain antibody fusion proteins for detection of Citrus tristeza virus - Terrada, E.; Kerschbaumer, R. J.; Giunta, Giuseppe; Galeffi, P.; Himmler, G.; Cambra, Mariano (2017)
Recombinant single-chain variable fragment antibodies (scFv) that bind specifically to Citrus tristeza virus (CTV), which cause the most detrimental viral disease in the citrus industry worldwide, were obtained from the hybridoma cell lines 3DF1 and 3CA5. These scFv were genetically fused with dimerization domains as well as with alkaline phosphatase, respectively, and diagnostic reagents were produced by expressing these fusion proteins in bacterial cultures. The engineered antibodies were successfully used for CTV diagnosis in plants by tissue print enzyme-linked immunosorbent assay (ELISA) and double antibody sandwich-ELISA. The fully recombinant ELISAs were as specific and sensitive as conventional ELISAs performed with the parental monoclonal and bodies, showing the usefulness of recombinant antibodies for routine detection of a virus in woody plants for the first time.